Analisis Kemampuan Pemahaman Konsep Matematis Peserta Didik Ditijau Dari Adversity Quotient - Isnaini Handayani; Afifah Fitria Ramadhani (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to analyze students’ mathematical conceptual understanding ability based on their adversity quotient. The indicators of mathematical conceptual understanding in this study are (1) to restate a concept, (2) classifying objects by their properties, (3) giving an examples and counter examples, (4) presenting concepts into various mathematical representation, (5) to use and choose the procedure properly, (6) applying a concept or algorithm in problem solving and (7) to develop the sufficient requirements of a concept. There are three types of adversity quotients in this study are quitter, camper, and climber. This is a descriptive qualitative research. The Subjects in this study were 106 people of natural science major, in second grade of high school in Jakarta. The instrument used was the test of mathematical conseptual understanding ability and adversity quotient questionaire. Data were analyzed by reducing data, presenting the data and making the conclusions. Based on the study, there are two students with quitter types, 60 students with camper types, and 44 students with climber types. This Research indicates that the mathematical conceptual understanding ability is moderate category and the type of students’ adversity quotient is classified as camper.